The Tanning Industry in Galicia: a Comprehensive View of its Presence in the Region in the 20th century - Otero Eiriz, Claudio (Madrygal. Revista de Estudios Gallegos, 2018)
The tanning sector was one of the main industrial activities in the history of Galicia. This conclusion can be drawn from the analysis of only two aspects, its levels of production and its spreading throughout the Galician region. As regards the former aspect, the Administration’s historical statistical series of industrial activity in Spain show that one out of four leather sheets produced in the country in the mid-nineteenth century came from Galician leather factories. Concerning the second aspect mentioned, the leather industry in Galicia is not just present in a specific area but spread throughout the region in such a way that one out of four municipalities and nearly every region (districts, counties), tanning factories have been set up. This article studies this extraordinary industrial location, aiming not only to identify specific leather factories which were present in every Galician municipality, but also to draw conclusions about the reasons for their location and the spreading of the tanning sector throughout the region.